2018
DOI: 10.1007/s00455-018-9911-x
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Changes in Community-Dwelling Older Adults

Abstract: Older adults may evidence changes in swallowing physiology. Our goals were to identify dysphagia risk in community-dwelling older adults with no history of dysphagia, and to compare swallowing physiology and safety between older and younger adults. Thirty-two older adults with no history of dysphagia were prospectively recruited and completed the Dysphagia Handicap Index (DHI), two trials of a 3 oz. swallow screen, and videofluoroscopy (VFSS). Self-ratings of swallowing function were compared to published norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Oropharyngeal dysphagia is characterized by two primary functional impairments: a) impaired swallowing safety, involving penetration or aspiration of material into the larynx and lower respiratory tract; and b) impaired swallowing efficiency, where poor bolus clearance leads to pharyngeal residue [8,9]. Although penetration-aspiration and residue are usually interpreted to represent impairment, several studies suggest that these phenomena may be seen in a small percentage of healthy adults on videofluoroscopic or endoscopic examination, with higher frequency in healthy older adults [10][11][12][13]. In order to better understand these apparent changes in swallowing function, it is also important to determine whether there are age-related changes in the underlying anatomy and physiology of swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…Oropharyngeal dysphagia is characterized by two primary functional impairments: a) impaired swallowing safety, involving penetration or aspiration of material into the larynx and lower respiratory tract; and b) impaired swallowing efficiency, where poor bolus clearance leads to pharyngeal residue [8,9]. Although penetration-aspiration and residue are usually interpreted to represent impairment, several studies suggest that these phenomena may be seen in a small percentage of healthy adults on videofluoroscopic or endoscopic examination, with higher frequency in healthy older adults [10][11][12][13]. In order to better understand these apparent changes in swallowing function, it is also important to determine whether there are age-related changes in the underlying anatomy and physiology of swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] As a result, various problems can occur, such as lateral sulcus residue, poor bolus formation and mastication during the oral phase, and vallecular residue and aspiration during the pharyngeal phase. [6,9]…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Beyon 31 , 33.9% of the participants complained of swallowing difficulties and 39.8% reported having aspirated food. De Lima Alvarenga et al 32 found that 21% of interviewees experienced choking episodes and Mulheren et al 33 found that 29% of interviewees reported mild to moderate swallowing difficulty.…”
Section: Discussionmentioning
confidence: 99%